Use of Online Active Methodologies in Higher Education - Bárcena-Toyos, Patricia (IGI Global, 2024)
This chapter presents the results of a study that examines the effects of an online gamification of the end-of-unit tests of a course in a master's degree. Learners completed a survey about the effects of the online gamified experience on their motivation and their progress and results in the course. Participants (n = 41) were in- or pre-service teachers, so the survey examined their teachers' sense of self-efficacy in terms of the application of active methodologies and ICTs in their classes after the gamified experience. Results show that the gamification had positive effects in terms of increasing motivation for the subject and, therefore, their perceived academic results. Also, participants felt more confident to use gamification in their classes. Results also showed significant differences in terms of motivation between nontraditional and traditional learners.
Es un capítulo del libro: Armie, M., Asensio, G., de los Ríos, M. C., & Jordán Soriano, A. (Eds.). (2023). New Perspectives in Teaching and Learning With ICTs in Global Higher Education Systems. IGI Global.
Keywords: online active methodologies; higher education; online gamification; Scopus